TINJAUAN SOSIOEKONOMI PEMANFAATAN FESES SAPI DENGAN TEKNOLOGI VERMICOMPOSTING - Ratnaningsih Ruhiyat; Dwi Indrawati; Etty Indrawati; Lailautsiami Lailautsiami (Journal of Environmental Engineering and Waste Management, 2018)
The Cibodas village is located in Pasir Jambu subdistrict at Bandung Regency, majority community livelihood edged is dairy cattle and agriculture. The problem of waste management in terms of cattle manure that could potentially produce methane (CH4) as one of the greenhouse gases (GRK), and when the cattle manure dumped into the River then it can pollute the rivers directly. The purpose of this study is to see how big the benefits of social and economic aspects of the utilization of cattle manure at the farmer scale. A series of Research include : 1) collect opinions and responses to ranchers, livestock farmers and administrators, by filling the questionnaire against the management of the cattle manure, 2) Observations of operational  at the process of vermicomposting  in two locations, namely in kampong Papak Manggu and kampong Injeman Cibodas village, during the activities of Demontration plot. The observed data covering 1) production process of vermicomposting (worm production and the weight of the raw materials, daily activities, results of casting, mass balance and quality of organic fertilizer) 2) Required total working hour of process of vermicomposting 3) Space and facilities requirement 4) cost and price analysis. The research show that vermicompost is suitable to be implemented in processing cattle manure, base on the following reason : a) cleaning of the environment b) minimum labor requirement c) providing  additional income d)  availability of organic fertilizer.